An overview on micro-meso manufacturing techniques for micro-heat exchangers for turbine blade cooling. (2nd January 2008) - Lambie, James Eugene John; Xi, Fengfeng; Tan, Bo; Jubran, B.A.
There is a growing interest in design and manufacturing of micro-heat exchangers embedded in turbine blades of the jet engine for turbine blade cooling. The pertaining manufacturing technologies fall under micro-meso manufacturing, including subtractive methods, additive methods, and near net shaping methods. The purpose of this paper is to provide an overview of micro-meso manufacturing methods under these three categories and discuss their suitability for potential use for mass manufacturing of the turbine blades with integrated micro heat exchangers. Through comparison, several methods are identified as potential candidates, including micro-EDM, micro laser machining, and micro casting.